Transiting the uncertainty: Development and transformative change facing the global crises - Barboza-Arias, Luis Miguel (2020)
This editorial presents a literature review of some of the most recent research on the relationship of uncertainty to socio-technical systems transformation. It offers an analytical framework to discuss an uncertainty perspective different from those risk-focused approaches. Such reflections raise issues around the leading role of adaptive governance in dealing with emerging global crisis. It concludes with some insights about transformative change and sustainability.